Is Metacognitive Training effective for improving neurocognitive function in patients with a recent onset of psychosis?. (December 2022) - Ruiz-Delgado, Isabel; Moreno-Küstner, Berta; García-Medina, Mónica; Barrigón, María Luisa; Gonzalez-Higueras, Fermín; López-Carrilero, Raquel; Barrios-Mellado, Irene; Barajas, Ana; Pousa, Esther; Lorente-Rovira, Esther; Grasa, Eva; Cid, Jordi; et al.
Highlights: First study assessing MCT effect on neurocognitive function in incipient psychosis. MCT improves verbal memory and reduce perseverative errors. MCT improves executive function considering different assessments. MCT improves attention. Clinical implications due to ease of application and good satisfaction with MCT. Abstract: The aims are to assess improvements in memory, attention and executive function in first-episode psychosis after Metacognitive Training (MCT). A multicenter randomized clinical trial was performed with two arms: MCT and psychoeducational intervention. A total of 126 patients with a diagnosis of psychosis, less than 5 years from the onset of the disease, were included. Patients were assessed two or three moments (baseline, post-treatment, 6 months follow-up) depending on the test, with a battery of neurocognitive tests (TAVEC, TMTA-B, CPT, WCST, Stroop and premorbid IQ). General linear models for repeated measures were performed. A better improvement in the MCT was found by an interaction between group and time in CPT Hit index, TMTB, Stroop, recent memory and number of perseverations of the TAVEC. Considering three assessments, a better improvement was found in non-perseverative, perseverative and total errors of the WCST and TMTB. The MCT is an effective psychological intervention to improve several cognitive functions.